EDUCAÇÃO DO CAMPO NO ENSINO SUPERIOR: DIÁLOGO ENTRE O POPULAR E O CIENTÍFICO NA PRODUÇÃO DO CONHECIMENTO NO CURSO DE LICENCIATURA EM PEDAGOGIA DO PRONERA/UFPB - Correia , Deyse Morgana das Neves (2016)
The following thesis analyses the knowledge production brought by pedagogical practices and final papers of the Bachelor's Degree Course on Pedagogy of the Educational National Program of Agrarian Reform developed by the Federal University of Paraíba during the years 2008 to 2011. The goal of this analysis is to identify possible changes and contradictions generated by the production of knowledge; following the dialogue between logic, knowledge and the everyday practices of both country subjects and the university's during the process of graduation in alternating times and learning areas. We presents the hypothesis that the relationship between farmers (also the countryside social movements) and teachers/researchers from the university fosters the challenge of creating new ways of knowledge production within the academic community, thus overcoming the individualistic and competitive mindset of the capitalist market and producing an emancipating type of knowledge, more in line with the social character of science. Another consequence of this relationship is the insertion of different theoretical-methodological incursions on the academy's production method. The research's data consists of two distinct, although complementary, techniques: interviews and epistemological analysis. The interview gathered memories and teachers‟ statements on the possibilities and difficulties of the complex interplay between scientific knowledge and folklore experienced during alternating pedagogical practices and final paper counseling. The epistemological analysis was applied to the final papers so as to reconstitute the internal logic of that knowledge production, identifying the articulation between techniques, methods, theories, relations between the subjects and objects of knowledge, world-view, and the ideological implications present in these researches. During this process we highlighted the influences of both the folklore and scientific knowledge on the papers and identified three different intercession locations: field experience and country work as a starting point and thematic universe of the research objects; emancipatory and practical interests guided the student authors‟ goals towards using scientific research as an avenue of change for their rural communities and the relationship between the researcher-subject, coming from a rural background, the subjects and the contexts, also rural farmers, turned research-action participants. On this study we establish that the dialogue between popular and scientific knowledge is fundamental on rural students‟ knowledge production and, supported in theory, practice and application, creates changes on knowledge both as activity and product, according to the concept of education, theoretical-methodological guidance of academic activities and the social role of college and science, thus legitimizing the construction of a popular college and therefore, a popular science.